Beyond advertising : creating value through all customer touchpoints - Wind, Yoram; Hays, Catharine, 1958- (Hoboken : Wiley, 2016)
'Radically alter the impact of your advertising by changing your mindset Beyond Advertising offers concrete advice for actions to take and mindsets to adopt that will radically alter the impact of advertising--both for advertising professionals and target audiences. An ambitious book with insight from over 200 leading executives, innovators, and academics, this text paints a picture of what the future of advertising may look like by 2020. Most importantly, it provides concrete guidance regarding the changes you can make to your approach in order to thrive in an evolving industry, and explains what you can do differently now to create effective advertising across all consumer touchpoints. Advertising relies upon the engagement of target audience members to be successful, and achieving this engagement is becoming both easier and more difficult as communication channels change to keep up with the latest technology. Retaining a dynamic, flexible approach to advertising--and understanding where to make changes to your methods--is the only way to stay relevant in such a quickly moving industry. Visualize the evolution of the advertising industry, and understand how it may change in the coming decade Avoid the mistake of failing to change your approach to advertising as the industry evolves Identify the concrete actions you can take right now to improve your results Discover the RAVES method of advertising Beyond Advertising is a forward-thinking text that every advertising professional needs to maintain a level of relevancy as the industry continues to evolve'--
'Over two-hundred of the world's most forward-thinking executives, innovators, and academics paint a picture of what the future of'advertising' could and should be by the year 2020. In this book they give concrete advice for actions to take and mindsets to adopt that will radically alter the impact of advertising on both advertisers and the people they seek to influence. The book will focus on three current examples: -'Advertising' is in the throes of a transformation that calls into question its most fundamental concepts, but very few marketers are doing anything different to adapt. - Marketers cannot simply continue doing what they've been doing and expect to succeed. - What to start doing differently now: create advertising that is Relevant and Respectful, Actionable, Valuable, Experiential, and offers a Surprising Story (RAVES) orchestrated across all touch points and the implications of this to the vision, objectives, strategies and organizational and network architecture of the involved firms'--
Machine generated contents note: Preface: Who Should Read This Book? Part I Overview: The Motivation for Change and the Necessity for Challenging Current Mental Models Chapter 1: The Five Forces Driving the Need for Change, and the Enablers to Do So Chapter 2: It's All in Your Head: Challenging Entrenched Mindsets about'Advertising' Part II Overview: A New Model of Advertising Chapter 3: Orchestrating Value Creation across ALL Touchpoints Chapter 4: Aligning Individuals, Organizations, and Society through Authentic and Compelling Brand Purpose and Initiatives for Win-Win-Win Impact Chapter 5: Making the Substance of Each Touchpoint, and Touchpoint Journey,'RAVES' Chapter 6: Designing Touchpoints to Leverage the Expanded Power of Context:'MADEs' Part III: What to Do Now to Get Ready For -- And Co-Create -- The Future Chapter 7 Embrace a Culture of Adaptive Experimentation Chapter 8: Leverage All Aspects of the Organizational Architecture to Effect Change or Start Fresh Chapter 9: Transcend Silos and Barriers with Aligned Objectives, Open Innovation, Network Activation and Network Orchestration Chapter 10: A Global Movement From and Beyond Advertising toward a More Desirable Future Appendix One The Backstory: The Wharton FoA Program and the Advertising 2020 Project Appendix Two: Planning and Conducting an Experiment Appendix Three: Example Worksheet Appendix 4: Advertising 2020 Collaborators Bibliography.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Advertising; Communication in marketing; Customer relations; BUSINESS & ECONOMICS -- Customer Relations; Advertising; Communication in marketing; Customer relations; Electronic books